Genome-wide Association Study Identifies Genetic Variants Associated With Early and Sustained Response to (Pegylated) Interferon in Chronic Hepatitis B Patients: The GIANT-B Study. (2nd February 2019) - Brouwer, Willem P; Chan, Henry L Y; Lampertico, Pietro; Hou, Jinlin; Tangkijvanich, Pisit; Reesink, Hendrik W; Zhang, Wenhong; Mangia, Alessandra; Tanwandee, Tawesak; Montalto, Giuseppe; Simon, Kris; Ormeci, Necati; et al.
Abstract: Background: (Pegylated) Interferon ([Peg]IFN) therapy leads to response in a minority of chronic hepatitis B (CHB) patients. Host genetic determinants of response are therefore in demand. Methods: In this genome-wide association study (GWAS), CHB patients, treated with (Peg)IFN for at least 12 weeks ± nucleos(t)ide analogues within randomized trials or as standard of care, were recruited at 21 centers from Europe, Asia, and North America. Response at 24 weeks after (Peg)IFN treatment was defined as combined hepatitis B e antigen (HBeAg) loss with hepatitis B virus (HBV) DNA <2000 IU/mL, or an HBV DNA <2000 IU/mL for HBeAg-negative patients. Results: Of 1144 patients, 1058 (92%) patients were included in the GWAS analysis. In total, 282 (31%) patients achieved the response and 4% hepatitis B surface antigen (HBsAg) loss. GWAS analysis stratified by HBeAg status, adjusted for age, sex, and the 4 ancestry components identified PRELID2 rs371991 (B= −0.74, standard error [SE] = 0.16, P = 3.44 ×10 –6 ) for HBeAg-positive patients. Importantly, PRELID2 was cross-validated for long-term response in HBeAg-negative patients. G3BP2 rs3821977 (B = 1.13, SE = 0.24, P = 2.46 × 10 –6 ) was associated with response in HBeAg-negative patients. G3BP2 has a role in the interferon pathway and was further examined in peripheral blood mononuclear cells of healthy controls stimulated with IFNα and TLR8. After stimulation, less production of IP-10 and interleukin (IL)-10 proteins and more production of IL-8 were observed with the G3BP2 G-allele. Conclusions: Although no genome-wide significant hits were found, the current GWAS identified genetic variants associated with (Peg)IFN response in CHB. The current findings could pave the way for gene polymorphism-guided clinical counseling, both in the setting of (Peg)IFN and the natural history, and possibly for new immune-modulating therapies. Clinical Trials Registation: NCT01401400. Abstract : This large multi-ethnic genome-wide association study (GWA) study identified single-nucleotide polymorphisms PRELID2 and G3BP2 associated with both short-term and long-term response to (pegylated) interferon in hepatitis B e antigen (HBeAg)-positive and HBeAg-negative chronic hepatitis B patients, respectively. If further corroborated, these single-nucleotide polymorphisms could aid in clinical counselling.